2017
DOI: 10.1002/hbm.23915
|View full text |Cite
|
Sign up to set email alerts
|

Structural connectivity of the amygdala in young adults with autism spectrum disorder

Abstract: Autism spectrum disorder (ASD) is characterized by impairments in social cognition, a function associated with the amygdala. Subdivisions of the amygdala have been identified which show specificity of structure, connectivity, and function. Little is known about amygdala connectivity in ASD. The aim of this study was to investigate the microstructural properties of amygdala—cortical connections and their association with ASD behaviours, and whether connectivity of specific amygdala subregions is associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 97 publications
(155 reference statements)
2
33
0
Order By: Relevance
“…In line with these observations is the finding that individuals on the autistic spectrum are less prone to the RHI (Cascio et al, 2012;Palmer et al, 2015). Moreover, previous studies found enlarged amygdala volumes (Gibbard et al, 2018) and increased amygdala response to social stimuli in this group of patients (Kleinhans et al, 2009). Last, higher levels of the hypothalamic peptide hormone oxytocin (OXT) are associated with stronger illusory body ownership (Ide and Wada, 2017), and we have previously shown that intranasal administration of OXT dose-dependently inhibits amygdala reactivity (Spengler et al, 2017) and modulates cross-modal sensory integration (Maier et al, 2019).…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…In line with these observations is the finding that individuals on the autistic spectrum are less prone to the RHI (Cascio et al, 2012;Palmer et al, 2015). Moreover, previous studies found enlarged amygdala volumes (Gibbard et al, 2018) and increased amygdala response to social stimuli in this group of patients (Kleinhans et al, 2009). Last, higher levels of the hypothalamic peptide hormone oxytocin (OXT) are associated with stronger illusory body ownership (Ide and Wada, 2017), and we have previously shown that intranasal administration of OXT dose-dependently inhibits amygdala reactivity (Spengler et al, 2017) and modulates cross-modal sensory integration (Maier et al, 2019).…”
Section: Introductionsupporting
confidence: 70%
“…The observed relationship between amygdala integrity and illusion experience accords well with clinical studies assessing body ownership in patients with autism spectrum disorder (ASD). In ASD patients, it has been found that amygdala volumes are enlarged (Rausch et al, 2018;Gibbard et al, 2018) and functional amygdala responses to social stimuli are increased (Kleinhans et al, 2009) compared with healthy controls. Intriguingly, these patients show reduced susceptibility to the RHI (Cascio et al, 2012;Palmer et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of neuroimaging studies suggests that alexithymia may be associated with reduced activation in a number of brain areas associated with emotion processing, specifically the amygdala, mirror neuron system related brain regions, the dorsomedial prefrontal cortex, and the right insula and precuneus [ 16 ]. Although more research is needed on the potential links to alexithymia in this population, autism is known to be associated with atypical neural connectivity, including in the amygdala and insula [ [17] , [18] , [19] ]. Consequently, it has been proposed that both autism and alexythmia may both be associated with a genetic vulnerability to atypical brain connectivity that can manifest as either “pure” autism, “pure” alexithymia, or co-occurring autism and alexithymia, depending on the exact networks affected [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Special attention regarding the similarities between both conditions has been paid to two particular brain structures mentioned above: the amygdala and the frontal lobes. Although differences are attenuated as subjects get older (Martens et al, 2009), the amygdala is disproportionately large in both ASD and WS Schumann et al, 2004;Martens et al, 2009;Mosconi et al, 2009;Murphy et al, 2012;Jarvinen et al, 2013;Gibbard et al, 2018). The amygdala shows atypical functional connections to several brain regions, specifically with the ACC, the PFC, and the OFC (all of which are implicated in cognitive processing, attention, and inhibition) (Martens et al, 2008;Dedovic et al, 2009;Haas et al, 2014;Gibbard et al, 2018), and importantly, with various components of the social brain, particularly, the frontal lobes (Meyer-Lindenberg, 2005;Paul et al, 2010;Jawaid et al, 2012).…”
Section: Socio-cognitive Similarities In Asd and Ws: Explanatory Hypomentioning
confidence: 99%
“…Although differences are attenuated as subjects get older (Martens et al, 2009), the amygdala is disproportionately large in both ASD and WS Schumann et al, 2004;Martens et al, 2009;Mosconi et al, 2009;Murphy et al, 2012;Jarvinen et al, 2013;Gibbard et al, 2018). The amygdala shows atypical functional connections to several brain regions, specifically with the ACC, the PFC, and the OFC (all of which are implicated in cognitive processing, attention, and inhibition) (Martens et al, 2008;Dedovic et al, 2009;Haas et al, 2014;Gibbard et al, 2018), and importantly, with various components of the social brain, particularly, the frontal lobes (Meyer-Lindenberg, 2005;Paul et al, 2010;Jawaid et al, 2012). A key component of the limbic system, the amygdala is a set of brain structures that support emotion and motivation, among other functions (see Rolls, 2015 for review), and is forefront in much of the research about the social (dys)function in both conditions (Stefanacci and Amaral, 2000;Meyer-Lindenberg et al, 2005;Haas et al, 2010;Paul et al, 2010;Jawaid et al, 2012;Zalla and Sperduti, 2013;Barak and Feng, 2016).…”
Section: Socio-cognitive Similarities In Asd and Ws: Explanatory Hypomentioning
confidence: 99%